Competitive anxiety levels of track and field athletes in rural area of Sabah - Joseph Nandu; Hasnol Noordin; Pathmanathan K. Suppiah; Abdul Muiz Nor Azmi (Persatuan Psikologi Malaysia, 2022)
The purpose of the study was to examine the competitive anxiety level of track and field athletes in remote areas of Sabah. A total of 213 male athletic athletes aged between sixteen to eighteen years have participated in this study. The participants' competitive anxiety levels before competition were assessed and classified into three categories: cognitive anxiety, somatic anxiety, and self-confidence. The Competitive State Anxiety Inventory (CSAI-2) was utilized in this study, and participants completed the questionnaire 60 minutes before the competition began. The data were analyzed by using a one-way analysis of variance (ANOVA). The results showed that field athletes were significantly better compared to track athletes in cognitive anxiety and self confidence, (p < .05). Nevertheless, there was no significant difference between track and field athletes on somatic anxiety, (p > 0.05). The study found that field events athletes can cope with anxiety better than track events athletes. Hence, it was essential for track and field athletes to get a proper training program regarding their psychological demands before the competition. Low anxiety and high confidence levels can contribute to improved performance in athletes.